2003
DOI: 10.2214/ajr.181.3.1810851
|View full text |Cite
|
Sign up to set email alerts
|

Adenomyosis: MRI of the Uterus Treated with Uterine Artery Embolization

Abstract: In patients treated with uterine artery embolization, MRI shows changes in areas of adenomyosis with a decrease in junctional zone vascularity in patients with thickening of the junctional zone greater than 20 mm. Devascularization may be related to the distribution of adenomyosis. The presence of adenomyosis should not be used as a contraindication to uterine artery embolization because most patients show clinical improvement after undergoing this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(39 citation statements)
references
References 31 publications
3
34
1
1
Order By: Relevance
“…Although minimally invasive therapies such as implantation of a levonorgestrel intrauterine system (LNG-IUS) and endometrial ablation or resection have been used to manage uterine adenomyosis their success rates vary with the depth of uterine adenomyosis infiltration, and long-term results remain unclear [12,21,22]. Studies showing the effect of UAE for uterine adenomyosis mainly describe successful short-term results [13][14][15][16][17]. Midterm results of UAE for uterine adenomyosis are reported by some authors as being disappointing with a high rate of recurrence of clinical symptoms [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although minimally invasive therapies such as implantation of a levonorgestrel intrauterine system (LNG-IUS) and endometrial ablation or resection have been used to manage uterine adenomyosis their success rates vary with the depth of uterine adenomyosis infiltration, and long-term results remain unclear [12,21,22]. Studies showing the effect of UAE for uterine adenomyosis mainly describe successful short-term results [13][14][15][16][17]. Midterm results of UAE for uterine adenomyosis are reported by some authors as being disappointing with a high rate of recurrence of clinical symptoms [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported symptomatic improvement after UAE in women with uterine leiomyomata and uterine adenomyosis, so investigators have proposed UAE for managing symptomatic uterine adenomyosis. Despite reports of successful short-term and midterm results of UAE for symptomatic uterine adenomyosis, there is still a paucity of longer follow-up results [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…These are caused by the activation of small, low-flow vascular circuits that are not detected at the time of treatment. The microcirculation of the myoma can be evaluated only with MR angiography and the use of contrast agents, techniques which are often very expensive and not always readily available [10].…”
Section: Discussionmentioning
confidence: 99%
“…Les premières études suggèrent des taux de récidive à moyen terme de 5 à 10 % [41,51]. L'adénomyose associée aux fibromes ou isolée constitue également une cause de récidive clinique à moyen terme [54,55]. L'absence d'amélioration clinique et l'augmentation de taille après une embolisation de fibromes techniquement satisfaisante, doit faire évoquer, même si cela est exceptionnel, le diagnostic de sarcome utérin [56].…”
Section: éChec Ou Récidive Après Embolisationunclassified